2021
DOI: 10.3390/su13084551
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Use Efficiency as a Strong Indicator of Nutritional Security and Builders of Soil Nutrient Status through Integrated Nutrient Management Technology in a Rice-Wheat System in Northwestern India

Abstract: Nutrient use efficiency is reported as a strong indicator of the buildup soil nutrient status for nutritional security of crops through an integrated nutrient management approach under a rice-wheat system. The data revealed that integrated application of manures and fertilizers reported maximum organic carbon (0.39%) in the treatment receiving 100% of the recommended dose of fertilizers (RDF) + farmyard manure and lowering the pH to 6.39. The maximum available N (360.8 kg ha−1) was found in 100% RDF + press mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…However, the increase in yields with the foliar application of micronutrients (Zn and Fe) and urea may be due to the fact that the exogenous supply of nitrogen fertilizer resulted in increased photosynthetic rate, synthesis of metabolites, assimilates and its translocation to grains thereby enhancing the growth, performance and value of oilseed crops. These results are in accordance with the research of some workers [23,26]. Further, the results also indicated that the combined application of micronutrients (Zn and Fe) with nitrogen followed by foliar sprays of micronutrients at 2 stages produced the highest grain and stover yield.…”
Section: Effect Of Zn Fe and Urea Foliar Application On Grain And Stover Yieldsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the increase in yields with the foliar application of micronutrients (Zn and Fe) and urea may be due to the fact that the exogenous supply of nitrogen fertilizer resulted in increased photosynthetic rate, synthesis of metabolites, assimilates and its translocation to grains thereby enhancing the growth, performance and value of oilseed crops. These results are in accordance with the research of some workers [23,26]. Further, the results also indicated that the combined application of micronutrients (Zn and Fe) with nitrogen followed by foliar sprays of micronutrients at 2 stages produced the highest grain and stover yield.…”
Section: Effect Of Zn Fe and Urea Foliar Application On Grain And Stover Yieldsupporting
confidence: 91%
“…In oilseed crops, the highest seed yield with an increased rate of micronutrients and Fe) and urea fertilization might be ascribed to an increased number of fertile p resulting in higher seed production and yield [23]. Zinc and iron application increa Effect of urea and micronutrient foliar spray on grain and stover yield (q ha −1 ) of Indian mustard.…”
Section: Effect Of Zn Fe and Urea Foliar Application On Grain And Stover Yieldmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were analyzed statistically using the SAS statistical program using one way ANOVA. Duncan's multiple range test was used for significance comparisons of means at a 0.05 level of probability when the F values were significant in a randomized block design [36].…”
Section: Discussionmentioning
confidence: 99%
“…It can also be seen that in irrigation water, percentage recovery was more than spiking amount as copper is already present in soil as micronutrient, which has been discussed in our recent manuscript. [43,44]…”
Section: Electron Affinitymentioning
confidence: 99%